Problematika Penjatuhan Sanksi Pidana terhadap Anak dalam Kasus Penyalahgunaan Narkotika - Veronica Agnes Walukow; Wenly R. J. Lolong; Reynold Simandjuntak (Wajah Hukum, 2026)
Drug abuse among children is a multidimensional issue that requires a legal response that is sensitive to the principle of the best interests of the child. This study examines the issue of imposing criminal sanctions on children who abuse drugs, focusing on efforts to harmonize the Child Protection Law and the Narcotics Law and the application of the concept of restorative justice. Based on a normative legal research method with a legislative and conceptual approach, this study examines various regulations, court decisions, and relevant legal literature. The findings show a gap between the rehabilitative principle mandated by the Child Protection Law and the practice in the field, which is still predominantly oriented towards punishment. Although diversion mechanisms and restorative justice have been prioritized, their implementation is still hampered by the low level of understanding among law enforcement officials, limited rehabilitation facilities, and strong social stigma. Synchronization between the repressive nature of the Narcotics Law and the protective orientation of the SPPA Law has not been optimally achieved, resulting in inconsistencies in the application of sanctions. This study concludes that there is a need to reformulate policies that place rehabilitation as the main focus, strengthen the capacity of officials in restorative justice, develop community-based rehabilitation models, and improve coordination among stakeholders. The recommendations proposed include revising regulations on diversion, establishing special rehabilitation institutions for children, and implementing public education programs to reduce social stigma. Consistent application of the principle of the best interests of the child is expected to create a more protective and rehabilitation-oriented juvenile justice system.